Combined Trabeculotomy and Trabeculectomy with Application of Mitomycin C in managing Primary Congenital Glaucoma: Doi: 10.36351/pjo.v38i2.1349 - Shoaib, Khawaja Khalid; Anwar, Sidra; Majeed Jawwad, Akhwand Abdul (Pakistan Journal of Ophthalmology, 2022)
Purpose: To determine the success of combined trabeculotomy and trabeculectomy with application of Mitomycin C in primary congenital glaucoma. Study Design: Interventional case series. Place and Duration of Study: Mughal eye hospital Lahore from January 2018 to December 2019. Methods: Twenty-four patients of primary congenital glaucoma were included. Secondary glaucoma and patients with corneal haze were excluded. Corneal diameter above 11.5, 12.5 and 13 mm (when combined with raised IOP) were considered indications for the surgery in neonates, at 1 year of age and at any age respectively. I-Care tonometer was used to measure IOP in all the cases. Trabeculotomy combined with Trabeculectomy plus MMC was performed in all cases. Procedure was successful if post-operative IOP was between 5 and 21 mm of Hg and stable optic nerve head at 3 months after surgery. Results: Mean age of the patients was 9.7 ± 7.6 months. Mean preoperative intraocular pressure (IOP) was 27.8 ± 4.4 mm of Hg. Mean post operative IOP was 13.5 ± 6.5, 17.8 ± 5 and 16.9 ± 4.8 mm of Hg on first day, at the end of one month and after 3 months respectively.Twenty-one (88 %) cases were successful based on the set criteria.Complications included non-identification of Canal of Schlemn, full thickness superficial flap with uveal show due to very thin sclera, hyphema, collapse of anterior chamber and choroidal detachment. Conclusion: Combined Trabeculotomy and Trabeculectomy with application of Mitomycin C is effective in decreasing IOP significantly. Key Words: Trabeculotomy, Trabeculectomy, Mitomycin C, Primary Congenital Glaucoma.